PSÖRİAZİSLİ HASTALARDA EKLEM TUTULUMUNUN KLİNİK VE RADYOLOJİK OLARAK DEĞERLENDİRİLMESİ - Serpil Savaş; Pınar Başak; Meltem Çetin (Archives of Rheumatology, 2000)
The aim of this study is to evaluate the joint symptoms clinically and radiologically in a group of patients with psoriasis living in Isparta region and to determine the ratio of peripheral joint, temporomandibular joint (TMJ) and sacroiliac joint involvement. For this purpose, 30 patients with psoriasis were included in the study. Peripheral arthritis occurred in 8 patients (26.7%). Six patients (20%) had asymptomatic sacroiliitis. When the patients with arthritis was classified according to Glandman’s categories, we have found that 5 patients (16.7%) had symmetric polyarthritis, 4 patients (13.3%) had spondylarthropathy, 1 patient (3.3%) had asymmetric oligoarthritis, 1 patient (3.3%) had distal interphalangial joint involvement and spondylarthropathy, 1 patient (3.3%) had symmetric polyarthritis and spondylarthropathy. Two patients (6.7%) had TMJ involvement clinically and radiologically. We detected a high number of joint involvement in our patients with psoriasis. We suggest that the dermatologists and the physiatrists should work together in the evaluation of the patients with psoriasis.